A case of extensive burn injury with hypercalcemia caused by calcium ion absorption from the wound dressing. Issue 1 (January 2020) - Asai, Hideki; Maegawa, Naoki; Urisono, Yasuyuki; Kawai, Yasuyuki; Okuda, Akinori; Takano, Keisuke; Tada, Yusuke; Osaki, Toru; Fukushima, Hidetada
Highlights: Extensive burn patients rarely suffer from hypercalcemia. A dressing material containing calcium alginate fibers can cause hypercalcemia in severe burn patients. Immediate removal of the dressing form can decrease blood calcium levels. Abstract: Due to abnormalities in bone metabolism and an inability to produce normal vitamin D levels in the skin, patients with extensive burns often present with hypocalcemia, not hypercalcemia. In this report, we present a rare case of acute hypercalcemia caused by silver-containing calcium alginate fibers as a dressing in a patient with extensive burn injury. The patient had been treated with oral calcium formulation because of hypocalcemia. We applied silver-containing calcium alginate fibers to raw surface area after the first skin grafting surgery, and the calcium level corrected for the serum albumin level continued to rise up to 15.4 mg/dl with this dressing form even after discontinuation of oral calcium preparations. Cessation of the use of this dressing resulted in a sharp drop in blood calcium levels. Therefore, we concluded that the cause of the hypercalcemia was the absorption of calcium ions eluted from the silver-containing calcium alginate fibers. Our findings suggest that dressings may cause hypercalcemia in patients with extensive burns, and that physicians should be attentive to the dressings used in burn wound care.